Pengaruh Brand Ambassador dan Desain Produk terhadap Minat Beli Produk Erigo (Survey Pada Followers Instagram @erigostore).docx - Timothy Rekso Diputra; Eddy Setyanto; Ahmad Zulfahmi (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2023)
The purpose of this study was to determine the effect of brand ambassadors and product design on the purchase intention Erigo’s fashion products. This study uses a quantitative research design. The population of this research is Instagram followers @erigostore. The number of samples is 100 respondents. The sampling technique uses purposive sampling using the respondent's criteria, namely the respondent's age is at least 15-35 years and followers Instagram @erigostore. The results of the partial test (t test) with a significant level of 5% show a significance result of 0.000 and 0.000 <0.05, which means that the brand ambassador and product design variables have a significant effect on purchase intention. In the results of the f test, a significant result is 0.000 <0.05, which states that the brand ambassador and product design variables together have a significant effect on the purchase intention Erigo’s fashion products.